Modeling and analysis of the monolihic microtransformer - Chew, Sue Ping (Universiti Malaysia Sarawak, UNIMAS, 2008)
This thesis addresses integration of monolithic transformer, which focused on the analysis and modelling of the chip especially at radio frequencies (GHz). the classical network analysis technique is used to driven two port parameters of the microtransformer. Thus, the equivalent circuit model is obtained through both measurement and simulation with scattering parameters extraction.